Detailing For Cast-In-Place Pile-Column Ductility ? Introduction - Andrew Budek (Deep Foundations Institute, 2007)
Reinforced concrete piles are used to carry foundation loads through considerable depths of soil to provide superstructure stability under gravity loads and lateral forces. The creation of cast-in-place (or cast-in-drilled-hole, i.e., CIDH) piles begins with the auger-drilling of a hole of the appropriate depth, into which a cage of reinforcing steel is placed (the cage length is generally equal to the depth of the hole, a construction joint being used to connect the in-ground pile with the superstructure). The pile is then finished by casting with concrete, and the superstructure then appended. The superstructure may either be a column (denoting the structure a pile-column), a column and cap beam, or a footing. Typical pile-column configurations are shown in Fig. 1 (a CIDH pile used in a footing would be similar in overall configuration to Fig. 1(b), with H=0). CIDH piles are well-suited for alluvial soil profiles with a deep water table; such conditions generally allow the auguring of a clean and regular hole.